Community Assistance in Cultivating IoT-Based Hydroponic Plants as an Effort to Improve Food Security in Baruyu Lasara Village, Batu Islands - Fauzi, Rahmad; Zendrato, Walsyukurniat; Historis Manao, Leonardus (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
The community assistance program for hydroponic cultivation based on the Internet of Things (IoT) was implemented in Baruyu Lasara Village, Tello Island, South Nias Regency. This initiative aimed to strengthen food security in coastal areas with limited agricultural land and freshwater resources. Using a participatory approach, the program involved socialization, technical training, implementation of an IoT-based Nutrient Film Technique (NFT) hydroponic system, and agricultural entrepreneurship mentoring. The results demonstrated a notable improvement in the community’s capability to independently manage hydroponic systems, achieving a 90% growth success rate for pakcoy and a 60% increase in water-use efficiency compared to conventional farming methods. Participants’ knowledge levels increased by 80%, and a hydroponic farmer group was established to ensure program sustainability. The initiative had positive impacts on local economic resilience, social collaboration, technological literacy, and environmental sustainability. Overall, the program successfully enhanced food self-sufficiency and served as an effective model for applying modern agricultural technologies in small island regions.